Analisis Pemasaran Agribisnis Lada (Piper Nigrum L) Di Desa Mangkauk Kecamatan Pengaron Kabupaten Banjar Kalimantan Selatan - Hastirullah Fitrah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
ABSTRACTThe purpose of this study is Knowing the pattern of marketing channels , analyze and share the marketing margin, and to analyze the level of marketing efficiency pepper in the Mangkauk village. Based on field observations and analysis of data tabulation is known that selling price pepper producer farmers of 50.000 IDR/Kg and the consumer final purchase price of 61,000 IDR, with the margin 11,000 IDR, and the share of 81.967%, the pattern of 1's, producers farmers to sell directly to the end consumer, profit of 10.800 IDR/Kg. Marketing patterns 2nd, there is a longer marketing chain, namely: farmer producers, traders and retailers. The selling price of pepper at the producers farmers level, same with a pattern 1's is 50.000 IDR/Kg, the selling price of traders level is 61.000 USD/Kg, and the selling price retailers level is 72.000 IDR/Kg, so that the end consumer buy at a price of 72.000 IDR /Kg. the level producer farmes, marketing margin of 69,44%, traders of 11.000 IDR, and share of 69,44%, and retailers of 22.000 IDR, with share of 84,722%. Gains derived by 10.300 IDR/Kg traders with a share of 14.305%, while retailer profits earned 10.800 IDR/Kg with a share of 84.722%. Value of marketing efficiency in pattern 1 by 1.97% and the 2 patterns, traders is 1.14% and 0.27% retailers, based on the results of these calculations the chain or the most efficient marketing channel is the retailer level, efficient because the value lies between 0.1% - 50%.